RE-LAYOUT PRODUCTION FACILITY BREAD USING FTC AND ARC METHOD IN PT. XYZ: RE-LAYOUT PRODUCTION FACILITY BREAD USING FTC AND ARC METHOD IN PT. XYZ - Prihono, Prihono (UNIPA PRESS, 2018)
Layout arrangements are vital for improving quality, productivity and corporate image. A production requiring multiple machines and a production process flow that is too long necessitates the preparation of a detailed layout in order that there is no transfer flow movement in the production process. This study aims to make the production process has a total minimum displacement moment and increase employee performance. From the analysis conducted at PT. XYZ that produce bread shows the existence of long distance, motion behind and congestion during material handling. The result of analysis by using method from to chart shows that the distance of material transfer distance is 73, 70 meter, total frequency of material transfer 35 times and mileage with total 1,901 meter. The result of analysis using activity relationship chart where spray & seeding (J) and split machine (K) departments were moved close to proofing room 1 (H1) and proofing room 2 (H2) facility, rack & pan 1 (I1) facility was moved near With rack, tray & pan cleanning (G) area facilities and the sieving flour (B) and formula room (D) departments being moved close to the process area 2 (C2) facility.